The American dream deferred (BROOKINGS INSTITUTION PR, 2018)
Senator Cory Booker (D-NJ) shares the story of his father's journey from poverty to middle-class prosperity, but says the bargain that helped his father and other workers achieve the American Dream is now broken. Sen. Booker reflects on the trends and practices contributing to stagnant wages in the United States, including a corporate culture that favors shareholder payouts over investments in workers; barriers to worker mobility, like non-compete clauses; and the "fissuring" of the workforce, as companies today are more likely to contract out labor to low-cost vendors rather than employ directly. Senator Booker calls for policies that will address these and related challenges, expand opportunity for all Americans, and restore the bargain for all who seek it